Pengaruh Literasi Keuangan, Kepercayaan dan Keamanan Terhadap Transaksi Pengguna QRIS pada Generasi Z di Desa Sukamulih Tasikmalaya - Miranda Maryam; Heidi Siddiqa (Yayasan Literasi Sains Indonesia, 2026)
The advancement of digital technology has shifted the payment system toward cashless transactions, one of which is through the Quick Response Code Indonesian Standard (QRIS), with Generation Z representing the most potential user group. This study aims to determine the effect of digital financial literacy, trust, and security on QRIS usage among Generation Z in Sukamulih Village, Tasikmalaya. Using primary data gathered from questionnaires and observations, the research data was processed through multiple linear regression analysis using the SPSS application.The t-test results indicate that digital financial literacy has a positive and significant effect on QRIS usage (t = 6.056; sig. = 0.000). The security variable also shows a positive and significant influence (t = 6.717; sig. = 0.000). However, the trust variable surprisingly shows a negative and significant effect on the utilization of QRIS (t = -5.004 sig. = 0.000 ). Through the F-test, it is proven that digital financial literacy, trust, and security simultaneously have a significant effect on QRIS usage ( F = 48.201;sig. < 0.001). The coefficient of determination (R2) value of 0.515 indicates that 51.5% of the variation in QRIS usage is influenced by these three variables, while the remaining 48.5% is explained by other factors outside this study. These findings emphasize the importance of strengthening digital financial literacy and ensuring payment system security to optimize QRIS adoption among Generation Z.